What Counts as Buddhist Historiography and Why Does It Matter? - Teiser, Stephen F. (JAOS, 2024)
This review article argues that John Kieschnick’s Buddhist Historiography in China (2022) constitutes a landmark in the field. The book covers a large swath of original sources, analyzes authorial strategies, and assesses the place of writing about the Buddhist past within the Sinocentric tradition of court-focused historiography. I point up the strengths of the book, identify its most significant chapters, and probe its interpretation of Buddhist historiography. I also suggest that, by including a broader range of genres within the ambit of Buddhist historiography, future scholarship might add perspectives that diverge from those of the centralized state and the Saṃgha.